2021
DOI: 10.1039/d1gc00949d
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical-mediated fixation of CO2: three-component synthesis of carbamate compounds from CO2, amines and N-alkenylsulfonamides

Abstract: An electrocatalyzed three-component cascade reaction of CO2, amines, and N-alkenylsulfonamides is developed, providing an environmentally friendly and efficient method of synthesizing a series of new carbamate compounds. This reaction meets...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…8 showed that the temperature corresponding to the maximum release intensity of gaseous products for the composites was around 350°C. The peak values of gas-phase products were mainly distributed between 3550-3750, 2800-3050, 2250-2400, 1500-1800, 950-1200 and 650-750 cm −1 , which were in agreement with previous reports [31]. The FTIR spectra of the gaseous products of the composites at 350°C were shown in Fig.…”
Section: Analysis Of Gas-phase Products Of Rpuf Compositessupporting
confidence: 91%
See 1 more Smart Citation
“…8 showed that the temperature corresponding to the maximum release intensity of gaseous products for the composites was around 350°C. The peak values of gas-phase products were mainly distributed between 3550-3750, 2800-3050, 2250-2400, 1500-1800, 950-1200 and 650-750 cm −1 , which were in agreement with previous reports [31]. The FTIR spectra of the gaseous products of the composites at 350°C were shown in Fig.…”
Section: Analysis Of Gas-phase Products Of Rpuf Compositessupporting
confidence: 91%
“…It was even observed obvious collapse of cell structure in RPUF/PA-Al30. This may be because PA could promote the foaming process, the active −OH in PA reacted with -N=C=O group in polyisocyanate to generate carbamate, which further decomposed and released CO 2 , resulting in uneven forces in all directions during the growth of bubbles in the foaming process [31].…”
Section: Analysis Of Cell Structure Of Rpuf Compositesmentioning
confidence: 99%
“…Substitution on 1and 2-positions did not significantly hamper the reaction and In 2021, Xiong et al designed a four-component reaction following a similar pathway involving double bond activation through the formation of an iodonium cyclic intermediate. 126 ortho-Amino styrene was the substrate of choice and ammonium iodide was selected as the iodide source via anodic oxidation. An in situ formed carbamate by the reaction between CO 2 and an amine acts as a nucleophile.…”
Section: Other Mechanismsmentioning
confidence: 99%
“…Electrochemical synthesis is recognized as an environmentally friendly way to construct various nitrogen-containing heterocycles under external chemical oxidant-free conditions . In this field, some impressive pioneering works have been made by Moeller, Xu, Zeng, Lei, Cheng, Pan, Zhang, and others . Continuing our interest in novel electrochemical methods for the synthesis of nitrogen-containing heterocycles, we herein report an electrochemical approach for the construction of bis-pyrazolo­[3,4- b :4′,3′- e ]­pyridines from readily available aromatic aldehydes and pyrazol-5-amines (Scheme c).…”
Section: Introductionmentioning
confidence: 99%